CONTRIBUTION OF NANOTECHNOLOGY AND NANOSCIENCE TO THE EMERGENCE OF A NEW TYPE OF CENTRALITY CALLED: "DIGITAL AND INTELLIGENT NANOCENTRALITY" - FERNANE, A.; TESSA, A. (Courrier du Savoir, 2017)
ABSTRACT Over the last two decades, urban-urban architects have noticed nanotechnology and nanoscience-induced changes in the functioning and layout of human settlements and their contemporary urban centralities. The aim of this article is to explain the changes brought about by the two recent specialties on contemporary urban centrality. It is the era of a new form of centrality called: Digital and intelligent nanocentrality composed of digitized and high intelligence equipment, meets the requirements of the new digital revolution, that took on a new impetus at the beginning of this twenty-first century in the majority disciplines. These nanocentralities are connected by virtual networks in the form of a "spider web" via last generation satellites. These nanocentralities will manage various problems, including, the supremacy of the urban on the territories and what it has generated as spreading and fragmentation, become unavoidable in most urban situations.